Comparing early parental warmth and effective management as predictors of child conduct and emotional problems - Villadsen, A (2016)
Introduction: Identifying aspects of parenting that are protective for child emotional and behavioural outcomes is important for informing parenting intervention. Attachment theory and social learning theory represent two major theories that propose different mechanisms for how parenting influences child functioning. The aim of this study was to compare dimensions of early positive parenting associated with these two theoretical frameworks as predictors of child conduct and emotional problems. Method: Data were from a US based longitudinal study (the Early Steps study, Dishion et al., 2008) following a sample of 731 toddlers from age 2 to 7.5, from low income families and at high risk of early onset of child problem behaviours. Associations between observed parenting (age 2-3 and age 5) and parent reported child externalising and internalising behaviour (age 3, 4, 5 and 7.5) were examined in structural equation models. Results: Parenting related to attachment theory ('warmth') had little short-term association with child outcomes, but over time this parenting dimension increasingly predicted lower levels of child problems. Parenting associated with social learning theory ('effective management') was related to lower child conduct and emotional problems short-term, but in the long-term it had no predictive effect on child functioning. Discussion: Differences between parenting dimensions in terms of their respective short-term and long-term effects might be explained by the underlying mechanisms linking parenting and child outcomes. Attachment theory emphasises internal and emotional processes, and these may be slow building but more enduring. Social learning theory proposes that behaviours are driven largely by external motivations and inspirations, and these might be relatively instantaneous but short-lived. Conclusion: Results of this study indicate that early childhood parenting associated with attachment theory is an important protective factor for children’s longitudinal outcomes. For enhancing longer term, more enduring outcomes, it is likely that parent intervention and prevention programmes in early childhood should emphasise programme components drawing on attachment theory. However, it would be necessary to test this before making any firm recommendations.